ANALYSIS OF FACTORS DRIVING RECIDIVISM IN GENERAL CRIMINAL OFFENDERS IN CLASS IIA BENGKULU CORRECTIONAL INSTITUTION - Muhammad Fajar Ramadhan; Syahrial Yuska (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to analyze the factors driving recidivism among general crime inmates at the Class IIA Correctional Institution in Bengkulu. Using a descriptive qualitative approach, data were collected through interviews, observations, documentation, and literature review. The findings show that recidivism is a multidimensional issue influenced by both internal and external factors. Internal factors include economic pressure, mental health conditions, and personal social challenges. External factors involve social stigma, discrimination, and the lack of effective reintegration support after release. The analysis is supported by Robert K. Merton’s Strain Theory and Howard Becker’s Labelling Theory, which explain how structural pressures and negative societal labeling can reinforce the tendency of former inmates to reoffend. The study concludes that addressing recidivism requires a more comprehensive and holistic rehabilitation approach. It emphasizes the importance of strengthening collaboration between families, communities, and government institutions to create inclusive support systems and sustainable reintegration opportunities for former inmates. Keywords: Recidivism; Prisoners; Strain Theory; Labelling Theory; Rehabilitation; Social Reintegration